Church-state separation, healthcare policy, and religious liberty - Audi, R (Oxford Uehiro Centre for Practical Ethics, 2014)
This paper sketches a framework for the separation of church and state and, with the framework in view, indicates why a government’s maintaining such separation poses challenges for balancing two major democratic ideals: preserving equality before the law and protecting liberty, including religious liberty. The challenge is particularly complex where healthcare is either provided or regulated by government. The contemporary problem in question here is the contraception coverage requirement in the Obama Administration’s healthcare mandate. Many institutions have mounted legal challenges to the mandate on grounds of religious freedom. The paper proposes a number of interconnected principles toward a resolution of the problem: for the institutional realm, specific principles for church-state separation and a principle concerning the protection of citizens’sense of identity; and for the ethics of citizenship in the conduct individuals, principles that provide an adequate place for natural (thus secular) reason in lawmaking and political decisions.